'More than customers': conceptions of students as partners held by students, staff, and institutional leaders. Issue 12 (1st December 2020) - Gravett, Karen; Kinchin, Ian M.; Winstone, Naomi E.
ABSTRACT: Students as partners (SaP) practices are emerging in today's universities as a means to offer a more participative agenda, and to transform institutional cultures within an increasingly economically driven higher education context. This study contributes to understandings of partnership approaches, which largely still remain under-theorised, through exploring the conceptualisation of SaP by institutional leaders, staff, and students. Drawing on data from concept map-mediated interviews, this article offers a counterview to recent studies that have depicted staff understandings of SaP to be firmly located within a neoliberal discourse. Rather, our interviews portray surprising overlaps within students' and leaders' conceptualisations of SaP, depicting recurrent themes of communication, dialogue, community, and enabling students to escape neoliberal constructions: to become 'more than customers'. This article ends with a consideration of how investigating the ways in which students and staff conceptualise SaP can be valuable, as partnership approaches become further prioritised in institutional strategies.